On your knees - Unknown (Tufts Archival Research Center, 2018)
Content Warning: Red and white image of three men--two of whom are wearing military clothing and one of whom is wearing a mortarboard--forming a line and kissing each other's bottom. The first in line is kissing money offered by an outstretched hand. This is a scan of one of four duplicate posters in the folder.; For more information on TARC's content warning policy please visit our website: https://tarc.tufts.edu/content-warnings-protocol-for-digital-archival-material